2006
DOI: 10.1111/j.2042-3306.2006.tb05555.x
|View full text |Cite
|
Sign up to set email alerts
|

Is improved high speed performance following frusemide administration due to diuresis‐induced weight loss or reduced severity of exercise‐induced pulmonary haemorrhage?

Abstract: Improvement of performance in the furosemide trials was due more to the weight-loss related effects of the drug than its apparent alleviation of EIPH. Further research is warranted with the same or similar project design, but with a larger sample size and with horses known to have more severe EIPH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…It has been speculated that furosemide-induced reductions in body weight are indicative of reductions in body water and intravascular fluid volume and that these reductions in body water and intravascular fluid volume attenuate the exercise-induced increase in pulmonary arterial blood pressure typically associated with exercise, with a consequent reduction in the incidence of alveolar capillary rupture and decreased hemorrhage. [13][14][15] The amount of weight lost by horses in the present study after furosemide administration was consistent with the amount of weight loss in horses administered furosemide under experimental conditions. [16][17][18] However, weight loss does not appear to be directly related to the mechanism by which furosemide prevents EIPH, in that we did not identify an association between amount of weight lost and prevention of EIPH in the present study.…”
supporting
confidence: 69%
“…It has been speculated that furosemide-induced reductions in body weight are indicative of reductions in body water and intravascular fluid volume and that these reductions in body water and intravascular fluid volume attenuate the exercise-induced increase in pulmonary arterial blood pressure typically associated with exercise, with a consequent reduction in the incidence of alveolar capillary rupture and decreased hemorrhage. [13][14][15] The amount of weight lost by horses in the present study after furosemide administration was consistent with the amount of weight loss in horses administered furosemide under experimental conditions. [16][17][18] However, weight loss does not appear to be directly related to the mechanism by which furosemide prevents EIPH, in that we did not identify an association between amount of weight lost and prevention of EIPH in the present study.…”
supporting
confidence: 69%
“…In total, 5653 horses were enrolled in the 17 studies included in this review . The number of horses in each study ranged from 3 to 3539 horses.…”
Section: Resultsmentioning
confidence: 99%
“…A later study by the same group testing fluid administration after furosemide but before exercise found BW losses ranging from 5.9 ± 0.9 to 11.5 ± 0.8 kg (Hinchcliff & Mckeever, 1998). Horses in an earlier study by Tobin et al (1978) produced 10.5 L of urine at the end of 4 hr after furosemide administration, and even more studies have found an average 2%–4% BW loss with furosemide administration (Butudom et al, 2004; Forro & Lindinger, 2006; Freestone et al, 1988; Pritchard et al, 2017; Warren, Lawrence, Brewster‐Barnes, & Powell, 1999; Zawadzkas et al, 2006). As BW for horses in the current study averaged around 530 kg, post‐furosemide administration expected BW losses should be around 10.6–21.2 kg or around 10–20 L of urine.…”
Section: Discussionmentioning
confidence: 99%
“…While veterinarians and trainers use the diuretic to reduce the incidence or lessen the severity of exercise‐induced pulmonary haemorrhage (EIPH), its efficacy is mixed (Hinchcliff, Morley, & Guthrie, 2009; Knych et al, 2018; Pascoe, McCabe, Franti, & Arthur, 1985; Sullivan, Whittem, Morley, & Hinchcliff, 2015). Additionally, administration can enhance performance (Hinchcliff, McKeever, Muir, & Sams, 1993; Sweeney et al, 1990; Zawadzkas, Sides, & Bayly, 2006), but whether this benefit is from the reduced EIPH severity or short‐term weight loss (Hinchcliff et al, 1993; Pritchard, Spooner, & Hoffman, 2017) is unclear.…”
Section: Introductionmentioning
confidence: 99%